Influencing factors of pain during ultrasound-guided puncture sclerotherapy for ovarian endometriotic cysts via transabdominal and transvaginal approaches - LI Yuanhua; TIAN Hongju; YANG Qian (陆军军医大学学报)
Objective‍　‍To investigate the influencing factors of pain during ultrasound-guided puncture sclerotherapy in the treatment of ovarian chocolate cyst (OEC). Methods‍　‍A retrospective cohort study was conducted on 209 OEC patients undergoing ultrasound-guided puncture sclerotherapy in our department from September 2021 to September 2023. Demographic data, medical history and surgical information were collected. According to surgical approach, they were divided into transabdominal surgery group (n=57) and transvaginal surgery group (n=152). Pain scores were assessed at 5 surgical time points: needle insertion, irrigation, displacement, sclerosis, and needle withdrawal. Pain scores were compared between the 2 groups at each surgical moment. According to the pain scores at the moments of needle insertion and replacement, the patients were divided into the no/mild pain group (pain score ≤3) and the moderate/severe pain group (pain score ≥4), and the related factors of the incidence of moderate/severe pain were analyzed. Results‍　‍There was no statistical difference in intraoperative pain between different surgical approaches (transabdominal/transvaginal) in treating OEC under the guidance of ultrasound. At the moment of needle insertion, significantly higher incidence of moderate/severe pain was observed in the patients with a body mass index (BMI) >23.9 kg/m² than those with BMI ≤23.9 kg/m², and those with a history of dysmenorrhea than those without (P<0.05). At the time point of displacement, BMI and history of dysmenorrhea had no correlation with the incidence of moderate/severe pain. Age, obstetric history, mode of delivery, time of menarche, menstrual volume, history of pelvic surgery, history of combined adenomyosis, size of cysts, duration of surgery, and surgical approach had no notable impacts on intraoperative pain. Conclusion‍　‍Different surgical approaches for ultrasound-guided puncture sclerotherapy of OEC have no effect on pain levels at various surgical moments. From the aspect of humanistic care, transabdominal puncture should be preferred. During needle insertion and displacement, particular attention should be given to the overweight patients and those with a history of dysmenorrhea, and appropriate pain intervention measures should be formulated.